2021
DOI: 10.1007/s10554-021-02502-x
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat volume is associated with preexisting atrioventricular conduction abnormalities and increased pacemaker implantation rate in patients undergoing transcatheter aortic valve implantation

Abstract: Epicardial fat tissue (EFT) is a highly metabolically active fat depot surrounding the heart and coronary arteries that is related to early atherosclerosis and adverse cardiac events. We aimed to investigate the relationship between the amount of EFT and preexisting cardiac conduction abnormalities (CCAs) and the need for new postinterventional pacemaker in patients with severe aortic stenosis planned for transcatheter aortic valve implantation (TAVI). A total of 560 consecutive patients (54% female) scheduled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In patients undergoing TAVI, Weferling et al . found that a larger EAT volume was independently associated with pre-existing first-degree AV block and new pacemaker implantation after TAVI (OR = 1.005; P = 0.035) [ 132 ]. Another study with a small sample size did not detect an association between EAT volume and the need for pacemaker implantation after TAVI [ 133 ].…”
Section: Section 3: Eat In Clinical Practicementioning
confidence: 99%
“…In patients undergoing TAVI, Weferling et al . found that a larger EAT volume was independently associated with pre-existing first-degree AV block and new pacemaker implantation after TAVI (OR = 1.005; P = 0.035) [ 132 ]. Another study with a small sample size did not detect an association between EAT volume and the need for pacemaker implantation after TAVI [ 133 ].…”
Section: Section 3: Eat In Clinical Practicementioning
confidence: 99%